Mechanical adaptation of brachiopod shells via hydration-induced structural changes - Johannes Ihli (Nature Portfolio, 2021)
Bioinspired materials require an understanding of how biomaterials achieve the materials properties. Here, the authors report on the load-bearing shell of Discinisca tenuis and explore how hydration changes the dry shell from hard and stiff to soft and flexible within minutes by reorganisation caused by organic matrix swelling.